Regional Economic Outlook, April 2015 : Stabilizing and Outperforming Other Regions. (Regional Economic Outlook, 2015)
Asia and the Pacific remains the global growth leader, albeit with a moderated pace of expansion since the global financial crisis. There is considerable diversity across the region: growth in China is slowing to a more sustainable pace, while in Japan a pickup in growth is expected. Non-oil commodity exporters have experienced sharply falling prices, while net importers have benefited from large changes in terms of trade. The April 2015 Regional Economic Outlook examines the volatility risks from this regional diversity, as well as Asia and Pacific's role in global value chains and the factors affecting financial integration in Asia.